Professional Medical Exams: Patient Engagement and Ethico-Legal A Considerations - Abdul Ghani Rahimoon, Syed Zulfiquar Ali Shah, Kashifullah Shabir, Saba Memon, Samar Raza, Surhan Uzair, Sabiha Arain (Pakistan Journal of Medical & Health Sciences, 2023)
Patients have been part of medical education since recruits trained. Healthcare students learn by seeing several patients. They should examine patients well to pass their finals. Live patients have been considered to validate undergraduate assessment more than actors and manikins and abnormal findings1. They reduce the requirement for skepticism when studying simulated patients. Staff, candidates, and patients approve of patients evaluating final-year students’ skills2. Real patients are cheap and sometimes available. Patients now are engaged in undergraduate and postgraduate education and evaluation. The legal and moral rights and obligations of participants in educational settings are not well established3.